JENIS BURUNG DI KAMPUS UNIVERSITAS TANJUNGPURA - Indra, Sutarto Kusuma; Kustiati, Kustiati; Rafdinal, Rafdinal (Jurnal Protobiont, 2020)
Quality degradation, modification, and habitat loss are significant threats to bird species. The natural habitat of birds has been modified into residential land and facilities to meet the needs of human life as happened at Tanjungpura University. This study aims to determine of birds species at Tanjungpura University. Observations were carried out from January to March 2019. The method used in collecting the data from bird was â€œEncounter ratesâ€ which was conducted in the morning starting at 6 â€“ 9 am and at 3 - 6 pm. The data obtained were analyzed with the formula of simple abundance scale and frequency of attendance. The birds found at Universitas Tanjungpura are 28 species classified into 23 genera, 17 families, and seven orders. Birds found to have an abundance order scale are classified into abundant, general, frequent and, unusual categories. Birds included in the abundant category are Collocalia fuciphaga and Passer montanus. The types of bird foods at Tanjungpura University consist of frugivore, insectivore, granivore, herbivore, carnivore, piscivore, omnivore, molluscivore, and nectarivore. The value of attendance frequency have range between 10-100%. The bird species with highest frequency of attendanceâ€™s value is Passer montanus, Pycnonotus aurigaster, Pycnonotus goiavier, Collocalia fuciphaga, and Anthreptes malacensis.